O jogo das narrativas: ranhuras do mundo, pelos diários virtuais e outros ambientes narratológicos do game The Sims - Marcos Elizio de Moura Braga (2009)
This research will work with the theme: Games and Narratives. Throughout this paper we follow a path, or rather a possible "narratological chain" that somehow, could give to players of The Sims, the possibility to express and address their everyday life throughdifferent narrative forms. In this path, we will look beyond the gameplay, and try to analyze the narrative possibilities of the official website of the game, and the publications of the "The Sims diaries", that are written by the players themselves about the life of their avatars. We will try to see throughout this research, how the players can express themselves, try new ways to interact and to be present in the world through one of severalpossibilities of digital storytelling.